Kale Ritual Processing in the Kalimusada as a New Balaganjur - Andi Pastika Putra; I Wayan Rai S; Kadek Suartaya (RIRAI Publisher, 2023)
Kalimasada is an experimental Balaganjur work from a new perspective. Experimental Balaganjur with a new perspective was created due to the reality that most of Balaganjur's creations are still guided by traditional principles. Therefore, the purpose of creating Balaganjur's work is to create experimental Balaganjur according to the creator's ideas by developing instrumentation, sound exploration, playing techniques, and searching for new timbres and appearances. The problem: what are the characteristics of kale composition as music?. Sources of data in this creation are carried out through interviews, video or audio documentation, and appreciating the Balaganjur performance directly. The process is qualitavelly analysed using the theory of the creation of works of art based on local wisdom, the theory of Hindu aesthetics, and the theory of creativity. The Results: The creation of Balaganjur's experimental work